Chronic Kidney Disease Circulating Calciprotein Particles and Extracellular Vesicles Promote Vascular Calcification: A Role for GRP (Gla-Rich Protein). Issue 3 (March 2018) - Viegas, Carla S.B.; Santos, Lúcia; Macedo, Anjos L.; Matos, António A.; Silva, Ana P.; Neves, Pedro L.; Staes, An; Gevaert, Kris; Morais, Rute; Vermeer, Cees; Schurgers, Leon; Simes, Dina C.
Abstract : Objective—: Inhibition of mineral crystal formation is a crucial step in ectopic calcification. Serum calciprotein particles (CPPs) have been linked to chronic kidney disease (CKD) calcification propensity, but additional knowledge is required to understand their function, assemblage, and composition. The role of other circulating nanostructures, such as extracellular vesicles (EVs) in vascular calcification is currently unknown. Here, we investigated the association of GRP (Gla-rich protein) with circulating CPP and EVs and the role of CKD CPPs and EVs in vascular calcification. Approach and Results—: Biological CPPs and EVs were isolated from healthy and CKD patients and comparatively characterized using ultrastructural, analytic, molecular, and immuno-based techniques. Our results show that GRP is a constitutive component of circulating CPPs and EVs. CKD stage 5 serum CPPs and EVs are characterized by lower levels of fetuin-A and GRP, and CPPs CKD stage 5 have increased mineral maturation, resembling secondary CPP particles. Vascular smooth muscle cell calcification assays reveal that CPPs CKD stage 5 and EVs CKD stage 5 are taken up by vascular smooth muscle cells and induce vascular calcification by promoting cell osteochondrogenic differentiation and inflammation. These effects were rescued by incubation of CPPs CKD stage 5 with γ-carboxylated GRP. In vitro, formation and maturation of basic calcium phosphate crystals was highly reduced in the presence of γ-carboxylated GRP, fetuin-A, and MGP (matrix gla protein), and a similar antimineralization system was identified in vivo. Conclusions—: Uremic CPPs and EVs are important players in the mechanisms of widespread calcification in CKD. We propose a major role for cGRP as inhibitory factor to prevent calcification at systemic and tissue levels. Abstract : Supplemental Digital Content is available in the text.